How stakeholders respond to airline sustainability signaling - a social media analysis - Setälä, Kaarle; Aarikka-Stenroos, Leena; Wright, Stephen J.; Grundström, Mika (Emerald, 2025)
Purpose The purpose of this study is to explore stakeholder responses to an airline’s sustainability signaling act. Responding stakeholders, their interpretations and feedback to the signal are studied in light of signaling theory and corporate social responsibility (CSR). Design/methodology/approach This study was conducted using the social media analytics approach. A total of 7,002 publications in the public domain were collected from the internet’s news services, blogs and major social media websites. These posts were subjected to content, sentiment and reach analyses. Findings Diverse stakeholder groups, ranging from industry professionals to societal influencers, responded via social media to a CSR-related press release, the main types being general influencers of society and those working in the aviation or tourism industry. The themes of responses ranged from sustainability, technical development and the future of transport to green transition policies. Hence, the press release as a signal was linked to other discussions prevalent in society. Sentiments of the publications were mainly neutral or positive, with very few negative responses from stakeholders. Many responses were supportive, and the critical responses did not contain accusations of greenwashing. Practical implications Environmental CSR communications are strategically important to companies operating in carbon-intensive industries. The public may view breakthroughs in technology as an efficient way of emissions reductions cascaded with improvements in processes and practices. Utilizing new technology also affects several stakeholders and creates new opportunities for them. Knowledge on the subject may influence the tone of discussion. Originality/value This study views a press release as sustainability-related signaling and examines stakeholder responses in social media, contributing to CSR and signaling research in the context of the airline industry by observing the signaling process over time along with the behavior of the actors involved.
Keywords: Aviation; CSR communication; Corporate sustainability; Social media analysis; Signaling theory; fi=Rehtori|en=Rector|